Computational studies of stable hexanuclear CulAgmAun (l + m + n = 6; l, m, n > 0) clusters. Issue 13 (7th March 2016) - Posada‐Amarillas, Alvaro; Pacheco‐Contreras, Rafael; Morales‐Meza, Sharity; Sanchez, Mario; Schön, J. Christian
Abstract : A DFT study was carried out on the ground state structures of ternary Cu l Ag m Au n ( l + m + n = 6) clusters, with the aim of investigating changes of thermal and kinetic stabilities as an effect of composition, as well as the composition dependence of the electrostatic potential, of stable planar structures. DFT optimizations were performed using the PBE functional and the SDD basis set. All the optimized structures adopt planar geometries with bent triangular structures. Calculated binding energy values are in the range 1.5–1.9 eV/atom, which shows their thermal stability. The predicted HOMO‐LUMO energy gap values are in the semiconductor region, providing a qualitative indication of a moderate kinetic stability. NBO analyses indicate the existence of two mechanisms promoting planar structural stability, one due to bonding‐antibonding orbital interaction, and the other one due to the well‐known spd hybridization. Wiberg indices were obtained showing interatomic bonding. Electrostatic potential calculations show the existence of nucleophilic attack regions preferentially around silver and copper atoms located at the vertices while electrophilic attack regions are found in the vicinity of gold atoms over the cluster plane. Apparently, charge transfer occurs toward gold from silver and copper atoms when the concentration is favorable in the proximity of gold atoms. In particular, if the small ternary clusters discussed here contain only one gold atom, then a high electron density is observed at the site of this gold atom. © 2016 Wiley Periodicals, Inc. Abstract : Density Functional Theory calculations elucidate the structure of 6‐atom ternary noble metal clusters. As similarly seen in the case of small bimetallic clusters, planar structures are found, with an energy gap consistent with semiconductor nanoparticles. The planarity of the ground state structures thus obtained is analyzed through the natural bond orbital scheme, and the electrostatic potential at different atomic sites is obtained to be employed as a reactivity descriptor.